Malignant pheochromocytoma - Mamarizaev Dilshod Yunusovich; Minnullin Irkin Rashidovich; Juraev Mirjalol Dehkanovich (Genius Journals, 2024)
Malignant pheochromocytomas are rare endocrine tumors that develop within chromaffin tissue, which definitely is quite significant. The diagnosis of malignancy particularly is based on neoplastic recurrence or the presence of metastasis in organs that lack chromaffin tissue, which is quite significant. The malignant pheochromocytoma is discussed in this article.
Keywords: malignant pheochromocytoma; endocrine tumors; surgery; scintigraphy